2011
DOI: 10.1038/emboj.2011.408
|View full text |Cite
|
Sign up to set email alerts
|

The structural basis of Edc3- and Scd6-mediated activation of the Dcp1:Dcp2 mRNA decapping complex

Abstract: The Dcp1:Dcp2 decapping complex catalyses the removal of the mRNA 5 0 cap structure. Activator proteins, including Edc3 (enhancer of decapping 3), modulate its activity. Here, we solved the structure of the yeast Edc3 LSm domain in complex with a short helical leucine-rich motif (HLM) from Dcp2. The motif interacts with the monomeric Edc3 LSm domain in an unprecedented manner and recognizes a noncanonical binding surface. Based on the structure, we identified additional HLMs in the disordered C-terminal extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
143
3
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(162 citation statements)
references
References 50 publications
11
143
3
3
Order By: Relevance
“…We therefore termed this previously unannotated ORF in S. pombe Edc1 (see below). Edc1 lacks structural domains; however, in addition to the conserved region that we identified above, it displays a highly positive N-terminal region and a conserved HLM-like region (Fromm et al 2012(Fromm et al , 2014 in the C terminus that could interact with the Edc3 LSm domain. This feature highlights the complexity and redundancy of the interaction network between mRNA decapping factors.…”
Section: Prs Interact With Dcp1 With µM Affinitymentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore termed this previously unannotated ORF in S. pombe Edc1 (see below). Edc1 lacks structural domains; however, in addition to the conserved region that we identified above, it displays a highly positive N-terminal region and a conserved HLM-like region (Fromm et al 2012(Fromm et al , 2014 in the C terminus that could interact with the Edc3 LSm domain. This feature highlights the complexity and redundancy of the interaction network between mRNA decapping factors.…”
Section: Prs Interact With Dcp1 With µM Affinitymentioning
confidence: 99%
“…In addition, in Saccharomyces cerevisiae the two intrinsically disordered decapping enhancers Edc1 and Edc2, which show limited sequence conservation with human PNRC2, have been identified (Dunckley et al 2001;Lai et al 2012). Importantly, for Edc3 (Harigaya et al 2010;Nissan et al 2010;Fromm et al 2012), Pat1 (Nissan et al 2010), Edc1 and Edc2 Steiger et al 2003;Borja et al 2011), and PNRC2 (Lai et al 2012), the activation of the decapping activity has been shown in in vitro, indicating that these proteins directly regulate catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 This suggests three different models for how RGG motif proteins might be interacting with eIF4G and its implication on global cellular translation (Fig. 1) 47 Interestingly, the Lsm domain of Scd6 is responsible for the interaction with Dcp2, 45 whereas RGG motif domain interacts with eIF4G. 1 There are two non-mutually exclusive possibilities for how Scd6 might stimulate decapping.…”
Section: Why Do So Many Rgg Motifmentioning
confidence: 99%
“…Efficient decapping by Dcp2 requires the essential activator Dcp1 and in metazoans the scaffolding protein Edc4 (Fenger-Gron et al 2005;She et al 2006;Eulalio et al 2007;Chang et al 2014). Coactivator proteins that further activate decapping and may target the decapping complex to specific RNA decay pathways have also recently been characterized, including the enhancer of decapping proteins (Edc1-3) and PNRC2 (Borja et al 2010;Fromm et al 2011;Lai et al 2012). The Dcp1/2 decapping complex functions as part of a highly evolved network of protein-protein interactions that regulates cap hydrolysis and the degradation of mRNA.…”
Section: Introductionmentioning
confidence: 99%